Engaging in Collaboration: A Team of Teams Approach. (2nd April 2016) - Young, Carol; Hill, Rachel; Morris, Greg; Woods, Fabiola
Abstract: Adapting a Team of Teams model to a school environment provides a framework for a collaborative team culture based on trust, common vision, purposeful conversations, and interconnectivity. School leaders facilitate collaboration by modeling teamwork, as well as transparency and adaptability, to create a positive school culture and thereby improve student performance .